ApoCIII-Lp(a) complexes in conjunction with Lp(a)-OxPL predict rapid progression of aortic stenosis. Issue 10 (13th February 2020) - Capoulade, Romain; Torzewski, Michael; Mayr, Manuel; Chan, Kwan-Leung; Mathieu, Patrick; Bossé, Yohan; Dumesnil, Jean G; Tam, James; Teo, Koon K; Burnap, Sean A.; Schmid, Jens; Gobel, Nora; et al.
Abstract : Objective: This study assessed whether apolipoprotein CIII-lipoprotein(a) complexes (ApoCIII-Lp(a)) associate with progression of calcific aortic valve stenosis (AS). Methods: Immunostaining for ApoC-III was performed in explanted aortic valve leaflets in 68 patients with leaflet pathological grades of 1–4. Assays measuring circulating levels of ApoCIII-Lp(a) complexes were measured in 218 patients with mild–moderate AS from the AS Progression Observation: Measuring Effects of Rosuvastatin (ASTRONOMER) trial. The progression rate of AS, measured as annualised changes in peak aortic jet velocity (Vpeak ), and combined rates of aortic valve replacement (AVR) and cardiac death were determined. For further confirmation of the assay data, a proteomic analysis of purified Lp(a) was performed to confirm the presence of apoC-III on Lp(a). Results: Immunohistochemically detected ApoC-III was prominent in all grades of leaflet lesion severity. Significant interactions were present between ApoCIII-Lp(a) and Lp(a), oxidised phospholipids on apolipoprotein B-100 (OxPL-apoB) or on apolipoprotein (a) (OxPL-apo(a)) with annualised Vpeak (all p<0.05). After multivariable adjustment, patients in the top tertile of both apoCIII-Lp(a) and Lp(a) had significantly higher annualised Vpeak (p<0.001) and risk of AVR/cardiac death (p=0.03). Similar results were noted with OxPL-apoB and OxPL-apo(a). There was no association between autotaxin (ATX) on ApoB and ATX on Lp(a) with faster progression of AS. Proteomic analysis of purified Lp(a) showed that apoC-III was prominently present on Lp(a). Conclusion: ApoC-III is present on Lp(a) and in aortic valve leaflets. Elevated levels of ApoCIII-Lp(a) complexes in conjunction with Lp(a), OxPL-apoB or OxPL-apo(a) identify patients with pre-existing mild–moderate AS who display rapid progression of AS and higher rates of AVR/cardiac death. Trial registration: NCT00800800 .